Hypocomplementemia in systemic sclerosis - R. Steele; M. Hudson; Y. Lu (Reumatismo, 2011)
To the Editor, We read with interest the paper recently published by Cuomo et al. (1) in your journal reporting on the associations between hypocomplementemia and disease status in systemic sclerosis (SSc). In their report, these investigators found that 16.5% of their study subjects had hypocomplementemia and that those with hypocomplementemia had significantly greater disease activity, severity as well as disability...